Effect of nonlinear electrodynamics on shadows of slowly rotating black holes* * Supported by the National Key R&D Program of China (2020YFC2201400) - Tang, Jiuyang; Liu, Yunqi; Qian, Wei-Liang [UNESP]; Yue, Ruihong (IOP Publishing, 2023)
In this study, we investigate the effect of nonlinear electrodynamics on the shadows of charged, slowly rotating black holes with the presence of a cosmological constant. Rather than the null geodesic of the background black hole spacetime, the trajectory of a photon, as a perturbation of the nonlinear electrodynamic field, is governed by an effective metric. The latter can be derived by analyzing the propagation of a discontinuity of the electromagnetic waveform. Subsequently, the image of the black hole and its shadow can be evaluated using the backward ray-tracing technique. We explore the properties of the resultant black hole shadows of two different scenarios of nonlinear electrodynamics, namely, the logarithmic and exponential forms. In particular, the effects of nonlinear electrodynamics on the optical image are investigated, as well as the image's dependence on other metric parameters, such as the black hole spin and charge. The resulting black hole image and shadow display rich features that potentially lead to observational implications.
Keywords: black hole shadow; nonlinear electrodynamics; slowly rotating black holes